2021
DOI: 10.1111/jpy.13214
|View full text |Cite
|
Sign up to set email alerts
|

Density‐dependence and seasonal variation in reproductive output and sporophyte production in the kelp, Ecklonia radiata

Abstract: The kelp, Ecklonia radiata, is an abundant subtidal ecosystem engineer in southern Australia. Density‐dependent changes in the abiotic environment engineered by Ecklonia may feedback to affect reproduction and subsequent recruitment. Here, we examined: 1) how the reproductive capacity of Ecklonia individuals in the field (zoospores released · mm−2 reproductive tissue) varied with adult density and time, and 2) how the recruitment of microscopic gametophytes and sporophytes was influenced by zoospore density at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 80 publications
0
16
1
Order By: Relevance
“…For example, Tatsumi and Wright (Tatsumi and Wright 2016) obtained an average of 5 female gametophytes mm −2 and 0.5 sporophytes mm −2 in a laboratory experiment after 14 and 30 days respectively, equating to a transition rate of 10%. Another study quantified the transition rate of E. radiata during June (austral winter) and November (austral summer) and found that the transition from female gametophyte to sporophyte was higher in winter, with 30-55% transition compared to 19-36% transition in summer (Tatsumi et al 2022). Notably, cultures were maintained under 12 °C in June and under 17 °C in November to represent ambient winter and summer water temperatures respectively in that study (Tatsumi et al 2022), suggesting that seasonality as well as a temperature may be important.…”
Section: Sporophyte Stagementioning
confidence: 99%
See 3 more Smart Citations
“…For example, Tatsumi and Wright (Tatsumi and Wright 2016) obtained an average of 5 female gametophytes mm −2 and 0.5 sporophytes mm −2 in a laboratory experiment after 14 and 30 days respectively, equating to a transition rate of 10%. Another study quantified the transition rate of E. radiata during June (austral winter) and November (austral summer) and found that the transition from female gametophyte to sporophyte was higher in winter, with 30-55% transition compared to 19-36% transition in summer (Tatsumi et al 2022). Notably, cultures were maintained under 12 °C in June and under 17 °C in November to represent ambient winter and summer water temperatures respectively in that study (Tatsumi et al 2022), suggesting that seasonality as well as a temperature may be important.…”
Section: Sporophyte Stagementioning
confidence: 99%
“…Another study quantified the transition rate of E. radiata during June (austral winter) and November (austral summer) and found that the transition from female gametophyte to sporophyte was higher in winter, with 30-55% transition compared to 19-36% transition in summer (Tatsumi et al 2022). Notably, cultures were maintained under 12 °C in June and under 17 °C in November to represent ambient winter and summer water temperatures respectively in that study (Tatsumi et al 2022), suggesting that seasonality as well as a temperature may be important. An effect of both seasonality and temperature on gametogenesis and transition to sporophyte has been previously demonstrated for kelp species (Lee and Brinkhuis 1988;Tala et al 2004;Murúa et al 2013).…”
Section: Sporophyte Stagementioning
confidence: 99%
See 2 more Smart Citations
“…The species could also readily contribute to the bulk ‘kelp biomass’ market targeted at fertiliser and alginate production, and perhaps as a source of nutraceuticals (e.g., fucoidan) 1,63 . The first studies targeting nursery cultivation methods for the species that underpin near and offshore cultivation are emerging 55,64,65 . Despite the extensive ecological knowledge of the species, its aquaculture potential is largely unknown.…”
Section: Priority Seaweeds For Cultivation and Knowledge Gapsmentioning
confidence: 99%